A Review of Postharvest Losses in Fruits and Vegetables in Nigeria: The Need for an Extension Strategy - O C Adebooye; A J Farinde (Journal of Agricultural Extension, 2015)
The paper reviewed cases of postharvest losses of fruits and vegetables in Nigeria and identified an extension strategy to stem the losses. The paper highlighted some harvesting and handling methods that can be presented through the extension services to the farmers to stem postharvest losses. To reach the Nigerian farmers, the paper suggested the use of target system approach will? integrated mass inedia approach, group contact method, all in combination to educate farmers on how to reduce postharvest losses. It was also obsserved that cooperative and collaborative efforts of governments, non- governmental organizations, corporations, individuals and groups are highly necessary in solving the problem of postharvest losses in Nigeria.